Estudo observacional e proposta de classificação etiológica das manifestações cutâneas incidentes, agudizadas ou relacionadas à pandemia de covid-19 e/ou à vacinação contra SARS-CoV-2 - Rostey, Renato Roberto Liberato (2022)
In this descriptive study, a careful clinical evaluation of patients with incident, exacerbated or related cutaneous manifestations of COVID-19 and/or vaccination against SARS-CoV-2 was performed. The main objective was to systematically record the skin lesions found and explore possible risk factors known to be associated with these lesions, with a view to establish a classification proposal based on groups of plausible etiological hypotheses for the occurrence of skin manifestations. A total of 108 patients were evaluated from July 2020 to July 2022 in two dermatology reference services located in the state of Mato Grosso. Of these, 86 (79,6%) had incident, exacerbated or COVID-19-related skin reactions, 15 (13,9%) had skin lesions exclusively after vaccination against SARS-CoV-2, and 7 (6,5%) had skin reactions related to both COVID-19 and the vaccine. A total of 143 distinct dermatological reactions were diagnosed, for which etiological hypotheses were established based on the clinical-evolutionary characteristics of the lesion, the use of concomitant medications and the temporal link with COVID-19 and/or with the vaccine against SARS-CoV-2. Previous information available in the medical literature supported the main causal inferences and the proposed classification model. The cutaneous manifestations observed were classified as peri-infectious and post-infectious immuneinflammatory reactions related to COVID-19 (62.2%); exacerbation, by COVID-19, of pre-existing skin diseases in the patient (4.2%); skin manifestations motivated by the socio-sanitary context of the pandemic (2.1%); adverse drug reactions to the treatment of COVID-19 (14%); and adverse skin reactions to vaccines against SARS-CoV-2 (17.5%). It is expected that this classification proposal can contribute to the clinical reasoning of professionals who are faced with dermatological lesions associated with COVID-19 or after active immunization against SARS-CoV-2 and, consequently, guide a clinical decision-making more assertive to patients.